Photo-crosslinkable chitosan and gelatin-based nanohybrid bioinks for extrusion-based 3D-bioprinting - ALARÇİN, EMİNE (TAYLOR & FRANCIS AS, 2022)
In the last decade, 3D-bioprinting has attracted attention due to its capability to produce complex scaffolds. The selection of suitable biomaterials for the bioink design is very important for the success of 3D-bioprinting. In this study, chitosan and gelatin were chemically modified into methacrylated chitosan (ChiMA) and methacrylated gelatin (GelMA) with the methacrylic anhydride in order to obtain crosslinking points on the polymeric backbone. The eligible bioinks were formulated with the layered double hydroxide nanoparticles (LDHs). The effect of changing the amount of LDHs on the printability of the bioinks was evaluated by using rheological analysis and printability test with the extrusion-based 3D-bioprinting. The bioinks were crosslinked under UV light. Mechanical, swelling, degradation properties, and cell-adhesion behaviors of the obtained ChiMA/GelMA nanohybrid scaffolds containing LDHs were investigated. Based on the rheology and the printing results, ChiMA/GelMA nanohybrid scaffold containing 5% LDHs (ChiMA-G5) was found to be the optimal bioink. Notably, compression strength, elongation at break, and elastic modulus of ChiMA-G5 scaffold were higher than neat and other ChiMA/GelMA scaffolds. In vitro cell culture studies showed that LDHs do not have any negative effects. These findings indicate that the developed ChiMA-G5 bioink has great potential as a bioink to utilize for tissue engineering applications.
Keywords: 3D-bioprinting; LDH; methacrylated chitosan; methacrylated gelatin; photo-crosslinked scaffolds; nanohybrid bioinks; nanoparticles; LAYERED DOUBLE HYDROXIDES; IN-VITRO; INTERCALATION; BIOMATERIALS; HYDROGELS; RELEASE